Drug Abuse, Relapse, and Prevention Education in Malaysia: Perspective of University Students Through a Mixed Methods Approach - Chie, Qiu Ting; Tam, Cai Lian; Bonn, Gregory; Wong, Chee Piau; Dang, Hoang Minh; Khairuddin, Rozainee (Frontiers in Psychiatry, 2015)
In recent years, there have been increasing accounts of illegal substance abuse among university students and professional groups in Malaysia. This study looks at university students’ perceptions about this phenomenon. Students from Malaysian universities were asked for their impressions about drug availability and abuse, as well as factors contributing to drug abuse and relapse. The questionnaire also inquired into their knowledge and views regarding government versus private rehabilitation centres, as well as their exposure to, and views about, school-based drug-prevention education. Participants were 460 university students from five Malaysian states: Penang, Selangor, Kuala Lumpur, Sabah, and Sarawak. Results showed gender differences in perceptions of relapse prevention strategies, as well as factors leading to drug abuse and relapse. Students also believed that drug education would be more effective if initiated between the ages of 11 to 12 years, which is slightly older than the common age of first exposure, and provided suggestions for improving existing programs. Implications of student perceptions for the improvement of current interventions and educational programs are discussed.